Clinical efficacy and imaging outcomes of unilateral biportal endoscopy with unilateral laminotomy for bilateral decompression in the treatment of severe lumbar spinal stenosis - Hu, Yutong; Fu, Hao; Yang, Dongfang; Xu, Weibing (Frontiers in Surgery, 2023)
Objective: To investigate the clinical efficacy and imaging outcomes of unilateral biportal endoscopy (UBE) with unilateral laminotomy for bilateral decompression (ULBD) in the treatment of severe lumbar spinal stenosis (LSS). Methods: We retrospectively analyzed 50 patients with severe LSS treated with UBE-ULBD from October 2018 to March 2021. Visual analog scale (VAS) for back and legs pain, Oswestry disability index (ODI), modified Macnab criteria, complications, hospital stay, preoperative and postoperative dural sac cross-sectional area (DSCA) and Schizas grade, mean angle of facetectomy and osseous lateral recess decompression rate were examined. Results: The mean follow-up period was 10.7 months. The mean hospital stay was 2.76±1.02 days. At the final follow-up, VAS for back pain and legs pain decreased from 7.22±0.95 to 1.74±0.53 and from 7.88±0.69 to 1.46±0.50, respectively; ODI decreased from 69.88±6.32% to 23.28±3.87%. According to the modified Macnab criteria, the results were excellent in 24 (48%), good in 22 (44%), and fair in 4 (8%). Excellent or good results (a satisfactory outcome) were obtained in 92% of the patients. There were 2 cases of complications of dural sac tear. The postoperative DSCA was significantly enlarged compared with that before surgery, from 44.74±9.85 to 126.86±14.81mm2. According to Schizas grade, the stenosis grade changes from preoperative grade C in 16 cases, grade D in 34 cases, to postoperative grade A in 40 cases, and grade B in 10 cases. The mean angle of facetectomy of the ipsilateral facet joint was 70.65±6.02°, contralateral was 65.18±5.33°. The decompression rate was 70.82±4.34% (ipsilateral side) and 71.37±3.65% (contralateral). Conclusions: UBE-ULBD has a good clinical effect in the treatment of severe LSS, and has achieved satisfactory results in spinal canal enlargement, undercutting of facet joints, and decompression effect. It is a safe and effective surgical for severe LSS.